2020
DOI: 10.1017/gheg.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking as a risk factor for tuberculous pleural effusion: a case-control study

Abstract: This study assessed the tobacco smoking-associated risk for tuberculous pleural effusion (TPE) in India. Ninety-two patients with TPE and 184 controls were randomly selected and assessed regarding their tobacco-smoking status and type, quantity and duration of tobacco used. Odds ratios (ORs) for the association of smoking cigarette, beedi and cigarette or beedi with TPE were 19.22 (p < 0.0001), 2.89 (p = 0.0006) and 4.57 (p < 0.0001) respectively. ORs for developing TPE increased with an increase in beed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…(8.5 percent). Pavit Tewatia et al [9] found that 42.3 percent of cases had cough, which is similar to our findings. According to Z. Wang et al [11], the most typical presentation of TPE is cough.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(8.5 percent). Pavit Tewatia et al [9] found that 42.3 percent of cases had cough, which is similar to our findings. According to Z. Wang et al [11], the most typical presentation of TPE is cough.…”
Section: Discussionsupporting
confidence: 92%
“…[10] According to our survey, the majority of participants (58%) were normal weight, followed by underweight (38%) and only 4% were overweight. Pavit Tewatia et al [9] found that 20.6 percent of the cases were underweight, which is equivalent to the 38 percent seen in this study. Patient presentation The most common complaint among participants (41%) was cough, followed by cough with fever (13%), chest discomfort with shortness of breath (10%), and cough with chest pain (11%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study was supported by Tewatia P et al which suggest that smoker and alcohol consumer had an independent association with TPE. 16 In our study Pleural fluid ADA and glucose was higher in lymphocytes predominant and was statistically significant at <0. 001.…”
Section: Discussionsupporting
confidence: 50%
“…Among active TB cases, the risk is two times higher for developing the disease and the chance of death is 2.6 times higher. It is also worth mentioning that the chances for development and worsening/death increase significantly with the time of consumption in years, the number of cigarettes used per day, and the socioeconomic level [28,29]. Tobacco use is a more common preventable risk factor for mortality and premature morbidity [30].…”
Section: Discussionmentioning
confidence: 99%